Compressive strength of lightweight foamed concrete with kenaf fibre of different treatment period - Chan, Jun Ming (2024)
As global concern for sustainability grows, the importance of sustainable practices in the construction industry has become increasingly significant. The construction sector, a major contributor to environmental impact, is increasingly focusing on adopting sustainable materials and methods. Among these efforts, enhancing the mechanical properties of concrete has emerged as a key area of research. Continuous advancements and discoveries aim to improve concrete's strength, durability, and overall efficiency, in line with the broader sustainability goals of the construction industry. Kenaf fibre (KF), derived from Hibiscus cannabinus L., is a byproduct of the textile industry. Incorporating KF into lightweight foamed concrete (LFC) not only addresses the waste and disposal issues associated with the textile industry but also enhances the concrete's strength properties. This study investigates the strength properties of lightweight foamed concrete incorporated with untreated kenaf fibre (UKF) and kenaf fibre treated with 1.5 M sodium hydroxide (NaOH) for 6, 9, and 12 hours (TKF 6HR, TKF 9HR, TKF 12HR). Compressive strength, splitting tensile, and flexural strength tests conducted to assess the strength of lightweight foamed concrete (LFC). Additionally, scanning electron microscopy (SEM) analysis was performed to examine the microstructure of LFC incorporated with KF. The findings reveal that while there is a 23.98% reduction in workability, the TKF 12HR results in increases of 19.46%, 24.93%, 38.33%, and 33.98% in 28 days compressive strength, residual compressive strength, splitting tensile strength, and flexural strength, respectively, compared to the control sample. Furthermore, SEM analysis shows that the treated fibre leads to better bonding between the fibre and the cement matrix. In summary, KF is a sustainable material that can effectively enhance the strength properties of LFC.